CEO BUSYNESS AND CLIMATE CHANGE DISCLOSURE: THE ROLE OF CORPORATE GOVERNANCE AND OUTCOME ON FIRM PERFORMANCE - Chandra, Budi; Robin; Cuandra, Fendy; Melysa (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2026)
Growing regulatory and stakeholder pressure underscores the importance of climate change reporting, yet the role of CEO busyness in shaping corporate disclosure remains underexplored. Prior evidence from other disclosure contexts is mixed, and few studies examine corporate governance as a moderating factor. This research investigates the influence of CEO busyness on climate change disclosure, the moderating effect of corporate governance, and the impact of disclosure on firm performance. Using 1,980 firm-year observations of IDX-listed firms from 2020 to 2023, the study applies panel data regression, Coarsened Exact Matching, Generalized Least Squares, and a two-stage Heckman model to ensure robustness. The results reveal that CEO busyness has a positive effect on climate change disclosure, strengthened by strong corporate governance. Moreover, climate change disclosure enhances firm performance. These findings extend Upper Echelons Theory by showing that busy CEOs can promote transparency, contrasting prior evidence suggesting negative effects.